Lyar Is a New Ligand for Retinal Pigment Epithelial Phagocytosis. Issue 10 (October 2015) - Guo, Feiye; Ding, Ying; Caberoy, Nora B.; Alvarado, Gabriela; Liu, Robert; Shen, Chen; Yu, Jisu; Zhou, Yixiong; Salero, Enrique; LeBlanc, Michelle E.; Wang, Weiwen; Li, Wei
ABSTRACT Phagocytosis is critical to tissue homeostasis, as highlighted by phagocytosis defect of retinal pigment epithelial (RPE) cells with debris accumulation, photoreceptor degeneration and blindness. Phagocytosis ligands are the key to delineating molecular mechanisms and functional roles of phagocytes, but are traditionally identified in individual cases with technical challenges. We recently developed open reading frame phage display (OPD) for phagocytosis‐based functional cloning (PFC) to identify unknown ligands. One of the identified ligands was Ly‐1 antibody reactive clone (Lyar) with functions poorly defined. Herein, we characterized Lyar as a new ligand to stimulate RPE phagocytosis. In contrast to its reported nucleolar expression, immunohistochemistry showed that Lyar was highly expressed in photoreceptor outer segments (POSs) of the retina. Cytoplasmic Lyar was released from apoptotic cells, and selectively bound to shed POSs and apoptotic cells, but not healthy cells. POS vesicles engulfed through Lyar‐dependent pathway were targeted to phagosomes and colocalized with phagosome marker Rab7. These results suggest that Lyar is a genuine RPE phagocytosis ligand, which in turn supports the validity of OPD/PFC as the only available approach for unbiased identification of phagocytosis ligands with broad applicability to various phagocytes. J. Cell. Biochem. 116: 2177–2187, 2015. © 2015 Wiley Periodicals, Inc.